A Novel PRRT2 Variant in Chinese Patients Suffering from Paroxysmal Kinesigenic Dyskinesia with Infantile Convulsion - Salem Baldi; Jin-Ling Zhu; Qing-Yun Hu; Ju-Li Wang; Jin-Bo Zhang; Shu-Hong Zhang (Behavioural Neurology)
PRRT2 mutations are the major causative agent of paroxysmal kinesigenic dyskinesia with infantile convulsion (PKD/IC). The study is aimed at screening PRRT2 gene mutations in patients who suffered from PKD/IC in Chinese population. Thirteen Chinese patients with PKD/IC were screened randomly for coding exons of the PRRT2 gene mutation along with 50 ethnically coordinated control people. Nine (2 unaffected) and 4 of the patients showed familial PKD/IC and apparently sporadic cases, respectively. We identified 5 different PRRT2 mutations in 10 individuals, including 8 familial and 2 apparently sporadic cases. However, no mutations were found in the 50 ethnically matched controls. Unknown (novel) NM_145239.2:c.686G>A and previously reported NM_145239.2:c.743G>C variants were identified in two familial and sporadic patients. All affected members of family A showed mutation NM_145239.2:c.650_670delinsCAATGGTGCCACCACTGGGTTA. The previously identified NM_145239.2:c.412 C>G and NM_145239.2:c.709G>A variants are seen in two individuals assessed in family B. Other than the previously identified variants, some of the patients with PRRT2-PKD/IC showed a new PRRT2 substitution variant. Thus, the spectrum of PRRT2 variants is expanded. The possible role and probability of PRRT2 variants involved in PKD/IC are highlighted.